2015
DOI: 10.1038/srep16151
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin coupled with HIF-1α/VEGF signaling pathways involved in galangin neurovascular unit protection from focal cerebral ischemia

Abstract: Microenvironmental regulation has become a promising strategy for complex disease treatment. The neurovascular unit (NVU), as the key structural basis to maintain an optimal brain microenvironment, has emerged as a new paradigm to understand the pathology of stroke. In this study, we investigated the effects of galangin, a natural flavonoid isolated from the rhizome of Alpina officinarum Hance, on NVU microenvironment improvement and associated signal pathways in rats impaired by middle cerebral artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…During homeostasis, endothelial Fzd4 deletion produces BBB compromise in adult mice 12 , whereas conditional deletion of endothelial Ctnnb1 in adult mice induces BBB breakdown and brain petechial hemorrhage, either through transcriptional activation or the adherens-junction functions of β-catenin 24 . During pathologic conditions, Wnt–β-catenin signaling in unfractionated brain tissue is correlated with tissue damage and hemorrhagic transformation after ischemic stroke 25,26 , and endothelial Wnt–β-catenin signaling is functionally implicated in the regulation of vascular integrity in glioblastoma 27 .…”
mentioning
confidence: 99%
“…During homeostasis, endothelial Fzd4 deletion produces BBB compromise in adult mice 12 , whereas conditional deletion of endothelial Ctnnb1 in adult mice induces BBB breakdown and brain petechial hemorrhage, either through transcriptional activation or the adherens-junction functions of β-catenin 24 . During pathologic conditions, Wnt–β-catenin signaling in unfractionated brain tissue is correlated with tissue damage and hemorrhagic transformation after ischemic stroke 25,26 , and endothelial Wnt–β-catenin signaling is functionally implicated in the regulation of vascular integrity in glioblastoma 27 .…”
mentioning
confidence: 99%
“…It has been suggested that Wnt signaling regulates VEGF, or vice versa, to control angiogenesis 4345 . It is possible that Wnt/β-catenin signaling is required for, or synergistically regulates, HIFα-activated VEGFA expression.…”
Section: Discussionmentioning
confidence: 99%
“…β‐catenin is excessively expressed in many cancer cells. Usually, β‐catenin contributes to cytoskeletal maintenance in co‐operation with actin, and the intracytoplasmic β‐catenin is controlled at a low level by proteasome‐dependent proteolysis controlled by a complex including axin, adenomatous polyposis coli (APC), glycogen synthase kinase‐3b (GSK‐3b), and casein kinase 1a (CK1a) (Wu et al., ). However, in many cancer cells, the degradation of β‐catenin is inhibited and β‐catenin is accumulated in the cytoplasm by an extracellular secretory glycoprotein called Wnt, which binds to the complex of Frizzled (Fz) and the low‐density lipoprotein receptor‐related protein (LRP) (Duchartre, Kim, & Kahn, ).…”
Section: Discussionmentioning
confidence: 99%